MyCrocrux - Sam-On, Muhamad Firdaus Syahmi; Aqilah Nadia; Ainul Farisyah; Jomain, Nur Izzah Atikah; Saad, Wan Zuhainis (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
MyCrocrux is a game where people can actually live in the virtual world by using their avatar and learns about microorganisms that live around us. This game will help people to gain more knowledge about microbiology and apply it in their daily life. This also can increase awareness in our society about pathogenic microorganisms that are harmful to us. Thus, we can avoid any diseases that cause from the microorganisms.